Sonic Traditions: Exploring the Gamelan's Influence on Contemporary Indonesian Music - Haryanti, Iwa Ridho (Peneliti.net, 2024)
This study explores the impact of the Gamelan, a traditional Indonesian ensemble, on contemporary Indonesian music within the cultural studies framework. The Gamelan, deeply rooted in Indonesia's musical heritage, serves as a dynamic bridge between tradition and modernity. By employing qualitative methods such as in-depth interviews and archival analysis, the study uncovers a symbiotic relationship between tradition and innovation, challenges to cultural dichotomies, and the Gamelan's multifaceted role in shaping cultural identity and resisting homogenization in the face of globalization. Results reveal the Gamelan's pivotal role in fostering cultural hybridity and innovation, enriching the global dialogue on cultural expressions. Symbolically, it constructs and expresses Indonesian cultural identity, emphasizing its resistance to cultural commodification. The study also addresses challenges related to appropriation and commercialization, emphasizing the importance of ethical approaches in integrating the Gamelan into contemporary music. Additionally, it highlights the Gamelan's impact beyond music, acting as a catalyst for community engagement, education, and cultural preservation. Overall, this research contributes nuanced insights to cultural studies, revealing the Gamelan's adaptive and resilient nature in shaping contemporary Indonesian cultural narratives.